2014
DOI: 10.1590/1414-431x20143754
|View full text |Cite
|
Sign up to set email alerts
|

A forced running wheel system with a microcontroller that provides high-intensity exercise training in an animal ischemic stroke model

Abstract: We developed a forced non-electric-shock running wheel (FNESRW) system that provides rats with high-intensity exercise training using automatic exercise training patterns that are controlled by a microcontroller. The proposed system successfully makes a breakthrough in the traditional motorized running wheel to allow rats to perform high-intensity training and to enable comparisons with the treadmill at the same exercise intensity without any electric shock. A polyvinyl chloride runway with a rough rubber surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 38 publications
(53 reference statements)
1
26
0
Order By: Relevance
“…Neurological deficits were rated on a scale of 0 to 18 according to the modified neurological severity scores (mNSS) [18]. A higher score represents a more severe infarction.…”
Section: Modified Neurological Severity Scoresmentioning
confidence: 99%
“…Neurological deficits were rated on a scale of 0 to 18 according to the modified neurological severity scores (mNSS) [18]. A higher score represents a more severe infarction.…”
Section: Modified Neurological Severity Scoresmentioning
confidence: 99%
“…In animal behavioral studies (e.g., including researches that investigate animal endurance locomotion), the desired display is usually triggered by external stimuli produced from an artificial system, in which specialized engines or devices were generally embedded to interact with animals (Webb, ; Krause et al ., ). With the help of these artificial interactors, locomotion has been extensively explored in many species (Romano et al ., ); examples include forced wheel running (Chen et al ., ) and treadmill running (Moraska et al ., ) for vertebrates' walking, wind tunnel (Nebel et al ., ) and swim tunnel devices (van den Thillart et al ., ) for birds flying and fish swimming. For insects with various movement strategies, such as crawling, jumping, or flying (Sane, ; Burrows & Sutton, ; Gunther et al ., ), the strategy for insect‐artificial interaction is complicated, such as the arena for crawling (Roessingh et al ., ) and flight mill for flying (Attisano et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Today, therapeutic exercise is the most common method of rehabilitation that can significantly reduce the severity of functional damage (14). Previous studies have shown the positive effects of exercise on physical recovery after stroke via improvement of muscle strength and tone, walking ability, and pulmonary functioning (15)(16)(17). These exercises usually include wheel running, voluntary and involuntary exercise, and forced treadmill running, all of which can contribute to motor function improvement (18).…”
Section: Introductionmentioning
confidence: 99%